Depression econometrics: A FAVAR model of monetary policy during the Great Depression - Pooyan Amir Ahmadi; Albrecht Ritschl (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
The prominent role of monetary policy in the U.S. interwar depression has been conventional wisdom since Friedman and Schwartz [1963]. This paper presents evidence on both the surprise and the systematic components of monetary policy between 1929 and 1933. Doubts surrounding GDP estimates for the 1920s would call into question conventional VAR techniques. We therefore adopt the FAVAR methodology of Bernanke, Boivin, and Eliasz [2005], aggregating a large number of time series into a few factors and inserting these into a monetary policy VAR. We work in a Bayesian framework and apply MCMC methods to obtain the posteriors. Employing the generalized sign restriction approach toward identification of Amir Ahmadi and Uhlig [2008], we find the effects of monetary policy shocks to have been moderate. To analyze the systematic policy component, we back out the monetary policy reaction function and its response to aggregate supply and demand shocks. Results broadly confirm the Friedman/Schwartz view about restrictive monetary policy, but indicate only moderate effects. We further analyze systematic policy through conditional forecasts of key time series at critical junctures, taken with and without the policy instrument. Effects are again quite moderate. Our results caution against a predominantly monetary interpretation of the Great Depression.
Keywords: N12; E37; E47; E52; C11; C53; 330; Great Depression; monetary policy; Bayesian FAVAR; Dynamic Factor Model; Gibb Sampling; Geldpolitik; Schock; Wirtschaftskrise; Reaktionsfunktion; Wirkungsanalyse; Schätzung; USA